Cumulative Live Birth Rates Following Stimulation With Corifollitropin Alfa Compared With hp-hMG in a GnRH Antagonist Protocol in Poor Ovarian Responders - Errázuriz, Joaquín; Romito, Alessia; Drakopoulos, Panagiotis; Frederix, Billie; Racca, Analissa; De Munck, Neelke; Tournaye, Herman; De Vos, Michel; Blockeel, Christophe (Frontiers in Endocrinology, 2019)
Background: Bologna criteria poor ovarian responders have a very low prognosis. Although, it has been proposed that LH supplementation could be beneficial in women with previous hypo-response to FSH. There are no studies comparing the cumulative live birth rates (LBRs) between corifoliltropin alfa (CFA) and highly purified human menopausal gonadotrophin (hp-hMG). Objective: To compare cumulative LBRs in Bologna poor ovarian responders undergoing ovarian stimulation with corifollitropin alfa (CFA) followed by hp-hMG versus hp-hMG alone in a GnRH antagonist protocol. Design: This is a retrospective cohort study. We included in total 917 poor responders fulfilling the Bologna criteria for poor ovarian response at a university-affiliated tertiary centre from January 2011 until March 2017. Patients were administered either fixed daily doses of 300-450 IU of hp-hMG (group A) or a single dose of 150 μg of CFA followed by daily injections of ≥300 IU of hp-hMG from Day 8 of stimulation until the day of ovulation trigger (group B), in a fixed GnRH antagonist protocol. Results: LBR after fresh embryo transfer were similar in group A 71/510 (14%) and B 42/407 (10%). Cumulative LBR per cycle was significantly higher in group A (16.9%) compared to group B (11.8%); (P = 0.03). However, logistic regression analysis showed no association between the type of gonadotropin administered and cumulative LBR. Only age was significantly associated with cumulative LBR (OR=0.93, P = 0.007). Conclusion: Cumulative LBR are similar in Bologna poor responders stimulated with CFA followed by hp-hMG compared to hp-hMG monotreatment in an antagonist protocol.